Gastroenterological symptoms and diet therapy in children with autism - I. A. Bavykina (Лечащий Врач)
Objective. To identify differences in the presence and severity of gastroenterological complaints in patients with ASD, depending on the eating style. Methods. The study included parents of 138 children diagnosed with ASD, 30 of whom are committed to HD for more than 6 months. The children ranged in age from 3 to 15 years. The children were divided into 2 groups depending on their eating style. The first group consisted of 30 patients who adhere to HD, the second included 108 people who do not have dietary restrictions.Results. Every second child with ASD had significant recurrent gastroenterological complaints (52,8%, 73 out of 138). Children who adhere to HDG have fewer gastroenterological complaints, and they are more rare, short-term, episodic, not violating the child's condition, while children who are not committed to using diet therapy, complaints are more often persistent and recurrent. Diarrhoea and bloating bother children on HD more often. The most common complaint in both groups is nausea (63,3% vs 62,9%). Children who do not have dietary restrictions have a wider range of complaints, among them: selectivity in food, bad breath. The presence of undigested food particles in the feces. Conclusion. Before including HD in the course of therapeutic measures for ASD, it is necessary to consult a gastroenterologist and conduct a clinical examination to clarify the presence of food intolerance in the child.